MON-482 Thyroid Tuberculosis - An Unlikely Diagnosis - Araújo, Alexandra Novais (J Endocr Soc, 2020)
Background: Mycobacterium tuberculosis (MTB) is an aerobic bacillus responsible for the most cases of tuberculous infection. Approximately one-third of the world’s population is infected. Tuberculosis (TB) of the thyroid gland is an unusual diagnosis with an estimated prevalence of 0.1 to 0.6%. The thyroid TB can mimic different pathologies (thyroid neoplasms, lymphoma, infectious or granulomatous thyroiditis, Graves’ disease or bacterial abscess) and the diagnosis can be easily disregarded, especially in non-endemic countries and if the patient doesn’t have systemic symptoms. The fine needle aspiration and histopathological examination, with acid-fast bacilli staining and TB culture, are the gold standard exams. Clinical Case: A 71-year-old female was referred to our Endocrinology department after a diagnosis of nodular thyroid disease. She had complaints of slight cervical discomfort, with 6 months of duration. She hadn’t personal or familiar relevant antecedents. At observation, a movable, elastic and non-tender nodule of 15mm at the right superior thyroid lobe was identified. Blood tests including a thyroid profile were normal. The neck ultrasound showed, at the right lobe of the thyroid, multiple solid nodules; the dominant had 18mm, was heterogeneous and had multiple calcifications. Moreover, lymph nodes with suspicious ultrasonographic features along the right internal jugular chain were reported. The patient underwent fine-needle aspiration (FNA) of the suspicious thyroid nodule and one lymph node. Results were respectively: non-diagnostic (Bethesda I) and reactive pattern. FNA was repeated on a different occasion and results were similar. Due to ultrasound suspicious of malignancy, a total thyroidectomy was performed and a lymph node from level IV was sampled for extemporaneous examination. Necrotizing granulomas were documented; the Ziehl-Neelson staining (ZNS) was negative; material was sent to microbiology. Following this finding, ganglion emptying was not performed. The thyroid histology showed tuberculoid type granulomas with lymphoid border and central necrosis. However, the ZNS was negative. The diagnosis was definitely established by a positive culture of the lymph node tissue and molecular detection, by polymerase chain reaction (PCR), of MTB. Pulmonary involvement was excluded and she started antituberculous agents planned for 9 months (rifampicin and isoniazid during 9 months and ethambutol and pyrazinamide for 2 months). Conclusion: Thyroid TB is a rare presentation of extrapulmonary tuberculosis. In presence of systemic or specific complaints or history of exposition the diagnosis may be suspected and confirmatory tests requested in order to ensure an adequate treatment. However, sometimes, histopathology remains a key step and the use of cultures improves the sensitivity and specificity of TB tests.